INFLUENCE OF GENERAL ALLOCATION FUND, SPECIAL ALLOCATION FUND, AND CAPITAL EXPENDITURE ON FINANCIAL PERFORMANCE OF LOCAL GOVERNMENT - Safira Andhini; Juniati Gunawan; Hung-Yi Chen (International Journal of Contemporary Accounting, 2023)
The goal of the research is to ascertain how capital expenditures, special allocation funds, and general allocation funds affect government financial performance as evaluated by regional financial independence. Through capital expenditure, special allocation funds, and general allocation fund, local governments can build infrastructure that will provide long-term benefits, provide services to the public, and develop regional investments. The Minister of Finance of the Republic of Indonesia in 2021 highlighted the very low realization of the regional government budget reports. The data used is the Financial Reports of the Regional Government, namely the budget as well as realization report, transfer to the region and village fund report, and regional government budget reports from Regencies and Cities of North Sumatra Province for 2017-2022. The population is 33 regencies aswell as cities in North Sumatra, with a total sample size of 198. Panel data regression using saturated sample approaches is the analytical approach used. Measurements for capital expenditures, special allocation funds, as well as variable general allocation funds are made using realized values represented in rupiah. This research also provides an international perspective to show that general allocation funds and capital expenditure have a significant positive influence on local government financial performance, and special allocation funds have a significant negative influence on local government financial performance.